Morphological structures and histochemistry of roots and shoots in Myricaria laxiflora (Tamaricaceae) - Li Linbao (De Gruyter, 2021)
Myricaria laxiflora (Tamaricaceae) is an endangered plant that is narrowly distributed in the riparian zone of the Three Gorges, along the Yangtze River, China. Using bright-field and epifluorescence microscopy, we investigated the anatomical and histochemical features that allow this species to tolerate both submerged and terrestrial environments. The adventitious roots of Myr. laxiflora had an endodermis with Casparian bands and suberin lamellae; the cortex and hypodermal walls had lignified thickenings in the primary structure. In the mature roots, the secondary structure had cork. The apoplastic barriers in stems consisted of a lignified fiber ring and a cuticle at the young stage and cork at the mature stage. The leaves had two layers of palisade tissue, a hyaline epidermis, sunken stomata, and a thick, papillose cuticle. Aerenchyma presented in the roots and shoots. Several Myr. laxiflora structures, including aerenchyma, apoplastic barriers in the roots and shoots, were adapted to riparian habitats. In addition, shoots had typical xerophyte features, including small leaves, bilayer palisade tissues, sunken stomata, a thick, papillose cuticle, and a hyaline epidermis. Thus, our study identified several anatomical features that may permit Myr. laxiflora to thrive in the riparian zone of the Three Gorges, China.